Adaptability Promotes Student Engagement Under COVID-19: The Multiple Mediating Effects of Academic Emotion - Zhang, Keshun; Wu, Shizhen; Xu, Yanling; Cao, Wanjun; Goetz, Thomas; Parks-Stamm, Elizabeth J. (Frontiers in Psychology, 2021)
In response to the COVID-19 pandemic, millions of students in China followed an emergency policy called "Suspending Classes without Stopping Learning" to continue their study online as schools across the country were closed. The present study examines how students adapted to learning online in these unprecedented circumstances. We aimed to explore the relationship between adaptability, academic emotion, and student engagement during COVID-19. 1,119 university students from 20 provinces participated in this longitudinal study (two time points with a two-week interval). The results showed that adaptability (the ability to respond to changes) and student engagement are significantly positively correlated with positive academic emotion and negatively correlated with negative academic emotion. Furthermore, adaptability not only directly predicts student engagement, but also affects student engagement through the chain mediation of positive academic emotion and negative academic emotion. The results contribute to the gap in knowledge regarding changes in students' learning in response to the outbreak. This study further explains the internal mechanisms mediating the relationship between adaptability and student engagement. It may provide references for educational researchers and universities in dampening the negative effects of COVID-19 on students' learning by improving their adaptability and developing positive academic emotions.